Upaya peningkatan literasi digital dalam program beasiswa cendekia Baznas (BCB) di kota Bogor - Yuniar, Hesti; Hamdani, Ikhwan; Ikhtiono, Gunawan (Komunika: Journal of Communication Science and Islamic Dakwah, 2022)
Increasing literacy is a nation’s goal to prosper the community, but in fact the survey on the For International Student Assessment (PISA) program in 2019, Indonesia found that Indonesia was ranked 62 out of 70 countries with low literacy outcomes, or was in the bottom 10 countries. In this revolutionary era, understanding digital literacy is the basis for progress in thinking and behaving. This study uses a qualitative research approach, relating to social facts in society, data collection techniques through interviews and observations. Strengthening digital literacy is the focal point of the BAZNAS Cendekia Scholarship (BCB) to form the best zakat generation, has intellectual capacity and is ready for a career. The results of the research are coaching programs in the fields of leadership, Islam, independence, volunteerism, and self-development through Zoom Meetings, Youtube, and Instagram, involving the contributions of campus mentors and teams, showing success in the level of student productivity and achievement. There were 1,160 achievements from a total of 476 student participants in 101 Indonesian campuses that were reported, where the achievements included scientific writings,speakers,business plans,poetry competitions,design competitions,outstanding students on campus,science olympiads,videography,MTQ,book writers ,publishing books,debates,content creators and podcasts. This means that students are able to fulfill the components of interpretation, collaboration, intervention, problem solving and self-reflection. Abstrak Peningkatan literasi menjadi sebuah cita-cita bangsa untuk mensejahterakan masyarakat, namun faktanya survei pada program For International Student Assesment (PISA) pada 2019, Indonesia mendapati ranking ke 62 dari 70 negara dengan tingkat hasil literasi rendah, atau berada di 10 negara terbawah. Di era revolusi ini, pemahaman literasi digital menjadi dasar kemajuan berpikir dan berperilaku. Penelitian ini menggunakan pendekatan penelitian kualitatif, berkaitan dengan fakta sosial di masyarakat, teknik pengambilan data melalui wawancara dan observasi. Penguatan literasi digital menjadi poin fokus Beasiswa Cendekia BAZNAS (BCB) untuk membentuk generasi zakat yang unggul, memiliki kapasitas intelektual dan siap berkarir. Hasil penelitian yaitu dengan program pembinaan di bidang kepemimpinan, keislaman, kemandirian, kerelawanan,serta pengembangan diri melalui Zoom Meeting, Youtube, dan Instagram, melibatkan kontribusi para mentor kampus dan tim menunjukan adanya keberhasilan pada tingkat produktivitas dan prestasi mahasiswa. Terdapat sebanyak 1.160 prestasi dari total 476 peserta mahasiswa di 101 kampus Indonesia yang dilaporkan, di mana prestasi tersebut meliputi karya tulis ilmiah, pembicara, business plan, lomba puisi, lomba design, mahasiswa berprestasi di kampus, olimpiade sains, videografi, MTQ, penulis buku, menerbitkan buku, debat, content creator, serta podcast. Maka hal tersebut menjadikan para mahasiswa mampu memenuhi komponen interpretasi, berkolaborasi, intervensi, pemecahan masalah serta refleksi diri.